Instalasi Mesin Sampah Plastik Untuk Teknologi Pengumpulan Dan Pemilahan Sampah Anorganik Berkelanjutan - Nasution, Mahliza; Prasetyo, Healthy Aldriany; Dalimunthe, Apip Gunaldi (Yayasan Nuraini Ibrahim Mandiri, 2024)
The potential for waste and biomass definitely exists in every region, because every day humans naturally produce waste to meet their needs. However, the potential for waste and biomass in each area is different in proportion to the population. As the population increases in each region, the potential for waste and biomass produced also continues to increase. This research aims to: (1) Create a design for sorting organic and inorganic waste, and (2) Find out how the organic and inorganic waste sorting equipment works. The waste used includes cardboard, leaves, paper, wood twigs and banana peels for organic waste, as well as plastic, bottles, iron, cans and plastic bottles for inorganic waste. After designing and testing the sorting tool, the conclusion was that the design of the tool with the three tool sensors used was successful in differentiating the types of organic and inorganic waste so that the organic waste valve or inorganic waste valve would open according to which type of waste detected it fell into which category, then Monitoring the contents of the trash can will appear on the LCD and the recommended distance for organic waste with a sensor is less than 27 mm and for inorganic waste with a sensor is less than 3 mm.